Influence of the short term preliminary occlusion on the dynamics of arterial blood flow and working capacity of the calf muscles - Poderys, J. (Education. Physical training. Sport, 1998)
Objectives: First, the peculiarities of reactive hyperemia depending on the time of the occlusion are investigated as well as it's character and preliminary filling with blood of the occluded limb blood vessels. Second, the influence of the preliminary occlusion on the local muscle capacity and on the muscle capacity during natural locomotion are analyzed. Method: Fourteen middle distance runners participated in the investigation. The arterial blood flow intensity in the calf was measured with the method of venous-occlusion plethysmography. The amount of blood flow was measured using electroplethysmograph EMPR-01, using Whitney type sensors while the subject was sitting comfortably. We conducted the four research series trying to reach the stated objectives: 1. The influence of the short term occlusion on the dynamics of arterial blood inflow of the calf muscles. 2. The dynamics of arterial blood flow in the reactive hyperemia phase after using of various methods of decreasing the amount of blood in the calf. 3. Calf muscle working capacity dynamics under the influence of A - the combination of "needle application" and decreased pressure, and B - 1 minute arterial occlusions. 4. The influence of the preliminary occlusion on the muscle working capacity during natural locomotion. Results and Conclusion: 1. Increase of the arterial blood circulation in the reactive hyperemia phase depends on the character and duration of the occlusion and the same time on the degree of filling with blood of the primary segment under occlusion. Mechanical factors, such as changes in prefusion pressure, preliminary filling of blood vessels also affect vascular resistance and the intensity of skeletal muscle blood flow during reactive hyperemia. 2. The peak blood flow readings are registered after occlusions conducted when the amount of blood in the limb decreased before the occlusion and the lowesr blood circulation readings are registered after occlusions done with the increased filling of blood vessels. 3. Having a goal to maximally activate limb muscle blood circulation using occlusion of minimal duration the optimal would be to conduct a 1 minute occlusion to the sitting person after first decreasing blood vessels filling. It is not important what method of decreasing the amount of blood in the limb is used. 4. A short term occlusion improves muscle blood flow and as a result local muscle working capacity and muscle working capacity during natural locomotion is improved. A short term preliminary occlusion can be used as a method for improving muscle working capacity.